New presentations and exacerbations of immune thrombocytopenia after coronavirus disease 2019 vaccinations: the Taiwan experience. (19th May 2022) - Chou, Sheng-Chieh; Chang, Yu-Cheng; Liao, Chun-Kai; Chen, Tsung-Chih; Sun, Kuo-Jui; Huang, Wei-Han; Wu, Yi-Feng
Abstract: Immune thrombocytopenia (ITP) is a condition that is distinct from thrombosis with thrombocytopenia syndrome (TTS) that may also occur after coronavirus disease 2019 (COVID-19) vaccinations. Previous reports revealed an increased ITP incidence after ChAdOx1, a vaccine for COVID-19. Our study aimed to highlight the key features of ITP after COVID-19 vaccination. From April to October 2021, we collected data on 23 patients, including nine men and 14 women, with ITP from five hospitals across Taiwan who received either the ChAdOx1 or mRNA-1273 vaccine before development or exacerbation of ITP. Our findings revealed that both ChAdOx1 and mRNA-1273 vaccines were associated with ITP. Many patients responded well to steroids and immune suppressants, which may also suggest that the nature of thrombocytopenia is more like ITP rather than TTS. Lack of thrombosis, low D-dimer level, and negative anti-PF4 result could help to exclude TTS, which is also a rare but a far more lethal condition.